Fraud in Financial Institutions - Riyan Pradesyah; Nawir Yuslem; Chuzaimah Batubara (AIBPM Publisher, 2021)
Fraudulent acts in financial institutions have often occurred, there are even some financial institutions who try to clarify related to the frauds that occur in these financial institutions. This study describes fraudulent acts that occur in conventional financial institutions, by taking data from the official websites of each financial institution, by reading reports Good Corporate Governance (GCG) of banks. Data collection from 2015-2019. The research conducted is descriptive quantitative research, where the researcher only describes the data obtained from the source. The results of the study found that there were fraudulent acts in financial institutions that experienced a decrease and an increase in tone. The results of the analysis carried out, that financial institutions need to understand the dangers of fraud in human resources, in order to prevent fraud from an early stage.